Unlocking Learning: Investigating the Replayability of Educational Games - Rose Oluwaseun Adetunji; Abejide Ade-Ibijola (International Journal of Computer Games Technology)
Recently, gamification has emerged as an effective approach to captivate users, particularly in the context of online education. Although there has been a rise in the recent surge of articles on gamification, there is still a lack of research on the impact of replayability. We conducted a systematic literature review to address this gap by elucidating the impact of replayability in educational games on learners’ behaviour in e-learning. The analysis of the investigations reveals the game elements that are predominantly utilised in the literature, and their corresponding effects on learners are identified and mapped. Moreover, we categorise these observed impacts of replayability on learners into six components: variety and performance, experience and nostalgia, learning, goals and completion, social aspect, and difficulty. Additionally, this study also examined the cognitive and affective behaviour of users in relation to replayability. The results of our comprehensive analysis of existing literature indicate that the study of replayability in educational games and its effects on learning is still at the outset. There is a scarcity of experimental tests and evidence in this area, with a prevailing tendency to primarily utilise educational games as external rewards. The study’s findings indicate that educational games that can be played multiple times have a substantial positive impact on learning outcomes and engagement. The study suggests that educators and game developers should prioritise the creation of games that include features supporting repeated play and diverse learning experiences.